Occurrence and molecular identification of liver and minute intestinal Flukes Metacercariae in freshwater fish from fang-Mae Ai agricultural basin, Chiang Mai province, Thailand - Chalobol Wongsawad (2018)
Background: Fang-Mae Ai Agricultural Basin is located in Fang and Mae Ai districts, Chiang Mai province. There are many aquatic species distributed in this area, especially snails, crabs, and fish, which can serve as the first and second intermediate hosts of several trematodes. The roles of these intermediate hosts as related to parasitic infections in the area are not known. Objective: We determined the occurrence of liver flukes and minute intestinal fluke metacercariae in freshwater fish from Fang-Mae Ai Agricultural Basin. We also identified of metacercariae by using HAT-RAPD PCR method comparing DNA profiles of parasites. Materials and methods: Liver flukes and minute intestinal flukes were studied from the Fang-Mae Ai Agricultural Basin between October 2009 and September 2010. Fish specimens were seasonally collected and each fish was digested and filtered. The metacercariae were collected and counted under a stereo microscope and identified based on morphological characters. The genomic DNA of all parasites was extracted and purified from adult flukes and metacercariae. All extracted genomic DNA was detected by HAT-RAPD PCR using arbitrary primers to comparing DNA profiles between adult flukes and metacercariae. Results: Five species of metacercariae were found. There were one species of liver fluke, Opisthorchis viverrini, and four species of minute intestinal flukes, viz. Haplorchis taichui, Haplorchoides sp., Centrocestus caninus, and Stellantchasmus falcatus. The prevalence of metacercarial infection was observed in the cool-dry season at 78.30%, followed by rainy and hot-dry seasons at 72.84% and 69.01%, respectively. The prevalence of trematodes were Haplorchoides sp. (37.43%), H. taichui (35.66%), C. caninus (3.80%), S. falcatus (1.40%), and O. viverrini (0.44%). Conclusion: Minute intestinal flukes accounted for high infection rates while, liver fluke, O. viverrini was of low infection rate. DNA profiles among metacercariae in Fang-Mae Ai Agricultural Basin correctly identified adult stages.